Assessment of Malaria, Anemia and Nutrition status of school-going children in the rural area of Charsadda, Pakistan - Zubair, Yasir; Zubair, Muneeba; Saeed, Usman; Bibi, Maryam; Ahad, Eidul; Ullah, Zeeshan; Gohar, Adam Khan; Shah, Usman; Rahman, Sadiq Ur; Rahman, Muhammad Iqbal Khan; Ullah, Shakir (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Malaria, anemia, and malnutrition are global health challenges with significant morbidity and mortality, and higher rates among children particularly in Africa. This study evaluated the prevalence and risk factors of malaria infection, anemia, and malnutrition among school-going children of Charsadda (a city of Khyber, Pakistan). A total of 400 children of aged 5-10 years were included in the study in 2023. Malaria infection was confirmed by rapid diagnostic tests. Hematocrit level was obtained using a centrifuge microhematocrit and converted to hemoglobin using standard conversion. Nutritional status was determined by the anthropometric measurements, and demographic characteristics were obtained by questionnaire. Anemia and malnutrition were defined according to the World Health Organization standards. Logistic regression analysis was used to determine association between the predictor variables and primary outcomes. In current research work 400 children were selected for the assessment of malaria and nutritional status, malaria infection was found more frequent among the students 120(12%). In addition, high prevalence of anemia 105(10.5%), malnutrition 90(9%), and stunting 70(7%) was observed, while wasting 2(0.2%) and underweight 20(2%0 had very low frequency. Malaria infection, anemia, and malnutrition were observed in12%, 10.5% and 9% of the children population, respectively. To the best of our knowledge, this is the first study showing the current health problems among the school-going children of district Charsadda the prevalence of malaria, anemia and malnutrition and their co-existence in children 5-10 years.